2015
DOI: 10.1007/s00404-015-3821-z
|View full text |Cite
|
Sign up to set email alerts
|

Cervical screening program and the psychological impact of an abnormal Pap smear: a self-assessment questionnaire study of 590 patients

Abstract: Cancer screening itself and abnormal test results have an impact on patient's feelings. To reduce the psychological impact, patients need to be better informed about the risks and benefits of cancer screening programs and in case of cervical cancer screening about the meaning of an abnormal test result. Our results underline the importance of a trustful physician-patient relationship in that matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 23 publications
(27 reference statements)
2
16
0
Order By: Relevance
“…Notification of an abnormal Pap smear finding psychologically impacts women, and previous research has aimed at assessing women’s health-related quality of life after such a notification [ 9 11 ]. These studies have highlighted that abnormal Pap smear findings evoke negative emotions ranging from anxiety to fear of developing or even having cancer [ 11 14 ]. The awareness of the infectious nature of HPV may even increase these emotions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notification of an abnormal Pap smear finding psychologically impacts women, and previous research has aimed at assessing women’s health-related quality of life after such a notification [ 9 11 ]. These studies have highlighted that abnormal Pap smear findings evoke negative emotions ranging from anxiety to fear of developing or even having cancer [ 11 14 ]. The awareness of the infectious nature of HPV may even increase these emotions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that among patients with dysplasia, Pap tests may be a source of additional office visits, procedures, and anxiety (69). No studies have specifically evaluated the anxiety associated with surveillance Pap tests among patients with a history of cervical cancer, but it is likely that these patients also experience a significant amount of anxiety associated with routine Pap tests for surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that notification of an abnormal Pap smear result can elicit negative emotions, such as anxiety and fear of cancer, among women (Dominiak‐Felden et al, ; Oscarsson, ; Rask, Oscarsson, Lindell, & Swahnberg, ; Rask, Swahnberg, Lindell, & Oscarsson, ; Thangarajah et al, ). These emotions can be increased by an awareness of HPV as a sexually transmitted infection and add feelings of blame, anger and fears of being stigmatised (Barnack‐Tavlaris, Serpico, Ahluwalia, & Ports, ; Rask, Swahnberg, et al, ).…”
Section: Introductionmentioning
confidence: 99%